A Path to Restorative Justice: Applicability of Mental Health Courts in the Philippines. (July 2021) - Guinigundo, Daniel Alberto G.
Described as 'situated at the intersection of the criminal justice, mental health, substance abuse treatment, and other social systems' 2, Mental Health Courts (MHCs) are courts that deal with specialized interventions for defendants with mental illness. Aside from presenting options other than incarceration, they provide a distinct avenue for collaboration between the public and private sectors in developing mechanisms to address law and policy concerns regarding prisoner mental health. Originating from the United States, MHCs offer an innovative and targeted response to the current Philippine situation. While the recent passage of the Mental Health Act by Congress in 2018 has brought the fatality of mental illnesses and disorders to the fore, several gaps remain unaddressed. This article seeks to rectify the existing lacunae in the legal and policy framework by proposing the establishment of MHCs in the country. This shall be undertaken in five phases: First, to justify the needed reform, data must be gathered to determine the number of inmates suffering from a mental illness; second, the enactment or revision of mental health legislation and court rules; third, craft strategic plans to address budgetary concerns, which shall be done through the Philippine Council for Mental Health, as the mandated regulatory agency; fourth, forge linkages with the public and private sectors to increase awareness through advocacy while equipping judges and concerned personnel through a series of trainings; and fifth, conduct pilot testing in certain courts and periodic evaluations to ensure sustainability.